2021
DOI: 10.1242/dmm.048901
|View full text |Cite
|
Sign up to set email alerts
|

Saturation mutagenesis defines novel mouse models of severe spine deformity

Abstract: Embryonic formation and patterning of the vertebrate spinal column requires coordination of many molecular cues. After birth, the integrity of the spine is impacted by developmental abnormalities of the skeletal, muscular, and nervous systems, which may result in deformities such as kyphosis and scoliosis. We sought to identify novel genetic mouse models of severe spine deformity by implementing in vivo skeletal radiography as part of a high-throughput saturation mutagenesis screen. We report selected examples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…CLCN1 mutations are reported to associate with myotonia congenita [ 34 ] and spine phenotypes [ 35 , 36 ]. Clcn1 knockout mice develop spine deformity, myotonia, muscle weakness, reduced growth, and brittle bones [ 37 ]. In this study, we found that CLCN1(NM_000083):c.763G>A(p.Gly255Arg) was carried by patient 7.…”
Section: Discussionmentioning
confidence: 99%
“…CLCN1 mutations are reported to associate with myotonia congenita [ 34 ] and spine phenotypes [ 35 , 36 ]. Clcn1 knockout mice develop spine deformity, myotonia, muscle weakness, reduced growth, and brittle bones [ 37 ]. In this study, we found that CLCN1(NM_000083):c.763G>A(p.Gly255Arg) was carried by patient 7.…”
Section: Discussionmentioning
confidence: 99%
“…SCUBE3 (signal peptide, CUB domain and EGF-like domain containing 3) is a protein coding gene. Diseases related with SCUBE3 include facial dysmorphism, short stature and skeletal anomalies with or without cardiac anomalies 2 and bone disease [ 42 ]. The gene encodes signal peptides, complement subcomponent C1r/C1s, Uegf, bone morphogenetic protein-1 as well as epidermal growth factor-like domains.…”
Section: Discussionmentioning
confidence: 99%
“…SCUBE3 (Signal Peptide, CUB Domain and EGF Like Domain Containing3) is a Protein Coding gene. Diseases related with SCUBE3 include Facial Dysmorphism, Short Stature and Skeletal Anomalies With Or Without Cardiac Anomalies 2 and Bone Disease [42].The gene encodes signal peptides, complement subcomponent C1r/C1s, Uegf, bone morphogenetic protein-1 as well as epidermal growth factor-like domains. Both full-length protein as well as the C-terminal fragment bind transforming growth factor TYPE II receptors to enhance epithelial-mesenchymal transformation and angiogenesis in tumors [43].…”
Section: Discussionmentioning
confidence: 99%